Pengesahan Instrumen Persekitaran Pembelajaran: Analisis Faktor Pengesahan (Sains Humanika, 2012)
This survey study was carried out to validate learning environment measurement model among engineering students. A total of 527 final semester engineering students were involved in this study. The variables presented in this study were good teaching, clear objectives, assessment, work load, learning resources and learning community. Data were analyzed descriptively for reliability (Cronbach Alpha values) and confirmatory factor analysis (CFA) was used to obtain 6 factor solutions using SPSS 17 andAMOS software. The results showed that the Cronbach Alpha was on the classification of high and very high which was higher than 0.70. Result of CFA confirmed 6 factors solution with data collected was fit with model. The study also proposed measurement model with 24 item measuring student perception on learning environments.
Keywords: Good teaching; clear objectives; assessment; work load; learning resources; learning community